Protestant Ghosts and Spirits of Capitalism: Ecology, Economy, and the Reformation Tradition. Issue 1 (March 2016) - Rowe, Terra S.
Abstract: This essay analyzes current Protestant perspectives on the relationship between this tradition and capitalism from the perspective of social and ecological concerns. Rather than deciding between the tradition's purity or culpability in the rise of capitalism, this essay suggests that those concerned with both the future of the tradition and social/eco‐justice must acknowledge both the tradition's congruence with global capitalism and the tradition's prophetic ability to critique and propose alternatives.